1987
DOI: 10.1111/j.1600-0447.1987.tb02765.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide patterns among physicians related to other academics as well as to the general population

Abstract: ABSTRACT— In the present study, we have followed a national cohort of physicians, academics and the general population (part of the compulsory census in 1960) for a period of 10 years and identified all cases of suicide during the period 1961 ‐ 1970. Furthermore, we have carried out a retrospective study of suicides among the four major medical specialist groups (general practioners, internists, psychiatrists and general surgeons) and compared these rates with other medical specialists.Results show an elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
7

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 10 publications
2
65
0
7
Order By: Relevance
“…A regional American study showed that female physicians had substantially higher lifetime rates of major depression (18). Moreover, other studies have shown high suicide rates for female physicians in Denmark (19), Finland (20) and Sweden (21).…”
Section: Discussionmentioning
confidence: 94%
“…A regional American study showed that female physicians had substantially higher lifetime rates of major depression (18). Moreover, other studies have shown high suicide rates for female physicians in Denmark (19), Finland (20) and Sweden (21).…”
Section: Discussionmentioning
confidence: 94%
“…They also concluded that psychiatrists had a higher probability of suicide than other specialties. Other studies [2,16] have not found an excess suicide rate among psychiatrists, or they have found that general surgeons were most at risk. As mentioned earlier, our data cannot be divided into specialties.…”
Section: Discussionmentioning
confidence: 96%
“…Überanstrengung durch den Beruf, das BurnoutSyndrom [4] und die psychiatrische Morbidität, insbesondere Depressionen sowie Alkohol-und/oder Tablettenmissbrauch angesehen werden. In einer schwedischen Untersuchung wurde für Ärztinnen eine 5,7fach erhöhte Rate im Vergleich zu anderen Frauen ermittelt [5]. Black gab an, dass 6,5 % aller Ärztinnen irgendwann im Laufe ihres Lebens Suizid begehen [6].…”
Section: Introductionunclassified